A Descriptive Study of Orgasm in Sexual Satisfaction and Intimacy among Females in India - R Vikhram Ramasubramanian; Veerabalajikumar (Archives of Medicine and Health Sciences)
Background and Aim: Orgasm is the peak of sexual arousal or behavior, whenever the peak of satisfaction is attained. Sexual satisfaction refers to the subjective experience of pleasure, contentment, and fulfillment related to one’s sexual activities and relationships and intimacy is the heart and soul of a close relationship. India is a diverse country with unique cultural, social, and economic factors that can impact women’s experiences in terms of intimacy and sexual satisfaction. The aim is to find out the relationship between orgasm in sexual satisfaction and intimacy among females in India. Materials and Methods: A descriptive research design is used for the present study. Through simple random sampling, 128 females who were married, people who can understand English, and who provided informed consent were selected for the study. The study was conducted from April 2022 to March 2023. The 20-item New Sexual Satisfaction Scale and the 36-item personal assessment of intimacy in relationships, and a semi-structured interview schedule were administered. Data were statistically analyzed using the statistical package for social services software, Version 26.0. A simple percentage analysis was used. The correlation was calculated for the variables. The Pearson correlation method was used to find the relationship between variables. A one-way ANOVA was employed to find out the significant mean difference between the demographic variables with a 95% confidence level, and P < 0.05 was considered statistically significant. Results: The result reveals that there is a relationship between intimacy and sexual satisfaction. Researchers found that there is a significant difference between sexual satisfaction and age, educational qualification, family type, place of living, and orgasm. Conclusion: There exists a positive correlation between intimacy and sexual satisfaction. This study helps to create awareness and promote intimacy, orgasm, and sexual satisfaction among Indian females.